Improving the understanding of emotional intelligence among academic staff in higher education in Malaysia - Samsuri, Nurshamimie Nabilah; Nik Md Salleh, Nik Sarina; Shamsuddin , Noorazzila; Pradesa, Hafid Aditya; Tanjung , Hasrudy; Jusoh, Mohd Sallehin (International Journal of Accounting, Finance and Business, 2024)
The primary goal of this study will be to determine whether self-awareness, empathy, and social skills impact academic staff in Malaysia. Identifying the key determinants affecting emotional intelligence will be crucial, especially given the ongoing changes in higher education teaching and learning. The study will focus on 367 academic staff from a higher education institution (HEI) in Malaysia who are directly involved in teaching and learning. Through correlational analysis, the study will explore how self-awareness, empathy, and social skills impact emotional intelligence. The results will inform recommendations to address the effects on academic staff, students, the institution, and the wider societal and national contexts.